Feasibility research of biodiesel production in Iceland made of Icelandic feedstock : comparison with other European countries - Sævar Birgisson 1973- (2013)
Biodiesel production in Iceland is an innovative industry while in most other countries, especially in other European countries, it has become developed commercial industry. With the use of Net Present Value (NPV) method, biodiesel production sourced from rapeseed oil (RSO) in Iceland and Scotland is compared according to different legal-, technical- end economic environment. With a change in assumptions for feedstock cost and prices of meal and biodiesel, but with same assumptions regarding plant capacity, years of operation, fixed cost, loan rates and production method. The NPV results where different between Iceland and Scotland. The NPV results in Iceland gives 14,4 million ISK (118 thousand USD) in NPV of equity and a 22% IRR of equity. While the NPV results in Scotland gives a minus 2,3 million ISK (minus 19 thousand USD) in NPV of equity and a 14% IRR of equity. With negative NPV and IRR below Minimum Attractive Rate of Return (MARR), project should be rejected. Estimated MARR was 15% for both Iceland and Scotland. Therefore, biodiesel production in Iceland, made from domestic feedstock of RSO is feasible while it is not in Scotland. Additionally, sensitivity analysis results indicate that price of biodiesel and a cost of feedstock is the most influencing factor for the final NPV outcome for both countries. This is in line with other studies, where feedstock cost represents up to 80% of the total operation cost. Nevertheless, market disequilibrium exists in Iceland where price for RSO as feedstock for cooking oil is much more valuable than for biodiesel production. KEYWORDS: Biodiesel; rapeseed oil; net present value; internal rate of return. Orkusjóður